Profil Media Pacota Pada Pembelajaran FPB dan KPK Di Sekolah Dasar - Sabila Cahyani, Putri; Wakhyudin, Husni; Adhi Prasetyo, Singgih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to produce Pacota media for FPB and KPK learning in elementary schools. The development of learning media in this media research uses the ADDIE research type (analysis, design, development, implementation, evaluation). Data collection techniques in this study were through observation, interviews, and questionnaires. The results of the data obtained from the validation of media experts were 97.33% with a very feasible category, the results of the validation of material experts were 80% with a feasible category, the results obtained from the teacher questionnaire were 92% with a very feasible category, and the results of the student response questionnaire were 96.52% with a very feasible category.